Speciation, toxicity mechanism and remediation ways of heavy metals during composting: A novel theoretical microbial remediation method is proposed. (15th October 2020) - Chen, Xiaomeng; Zhao, Yue; Zhang, Chuang; Zhang, Duoying; Yao, Changhao; Meng, Qingqing; Zhao, Ran; Wei, Zimin
Abstract: Heavy metals (HM) pollution is a major limitation to the application of composting products. Therefore, mitigating the toxicity of HM has attracted wide attention during composting. The toxicity of HM is mainly acted on microorganisms during composting, and the toxicity of different HM speciation is obviously various. There are many pathways to change the speciation to reduce the toxicity during composting. Therefore, in this review, the speciation distribution, toxicity mechanism and remediation ways of HM during composting were discussed in order to better solve HM pollution. The microbial remediation technology holds enormous potential to remediate for HM without damaging composting, however, it is hard to extract HM. The innovation of this review was to outline microbial remediation strategies for HM during composting based on two mechanisms of microbial remediation: extracellular adsorption and intracellular sequestration, to solve the problem how to extract microbial agents from the compost. Ultimately, a novel theoretical method of microbial remediation was proposed to remove HM from the compost. Graphical abstract: Image 1 Highlights: Speciation of heavy metals is sensitive to environmental factors during composting. A theoretical microbial remediation method is proposed to remove heavy metals. This will provide theoretical support for the application of microbial remediation.